"Sassy Queens": Stylistic orthographic variation in Twitter and the enregisterment of AAVE. (18th July 2019) - Ilbury, Christian
Abstract: Recent computational sociolinguistic analyses of social media have emphasized the potential of using orthographic variation as a proxy for speech, thereby permitting macro‐level quantitative studies of regional and social variation (e.g. Eisenstein, 2015). However, the extent to which stylistic variation may affect these analyses remains largely unexplored. In this paper, I explore how authors use variant spellings stylistically to deploy personae and characterological figures (Agha, 2003), by examining the presence of African American Vernacular English (AAVE) features in a corpus of 15, 804 tweets extracted from the timelines of 10 gay British men. I argue that the stylization of AAVE signals the development of a very specific persona—the "Sassy Queen"—which relies on an essentialized imagining of Black women as "fierce" and "sassy." Concluding, I emphasize the value of micro‐level analyses in complementing quantitative analyses of linguistic variation in social media.